Utilizing Online Paraphrasing Tools to Overcome Students’ Paraphrasing Difficulties in Literature Reviews - Siti Drivoka Sulistyaningrum (Journal of English Language Studies, 2021)
One of the prevalence of digital technology in academic writing, particularly in literature reviews, is the use of paraphrasing tools.However, there is a lack of research focusing on overcoming students' paraphrasing difficulties in writing.Using the notion of Schuemann, C., Byrd, P., & Reid. (2006), this paper explores students’ difficulties with paraphrasing and the use of online paraphrasing tools. A descriptive qualitative approach was used to collect data from 30 students enrolled in the Magister's of English Language Education (MELE) study program. Students' responses to two types of questionnaires were used as data sources. The study found that 83percent of the paraphrasing tools were used to rewrite the source text. Then, the most difficulties in terms of content, structure, language, and paraphrase strategy are paraphrasing itself, using correct grammar and appropriate vocabulary, and redundant/un-variative words. Furthermore, online paraphrasing tools mainly assist students in using the appropriate parts of speech (3.88) and in selecting appropriate vocabulary (3.79). It can then rewrite the source text using the same idea but a different writing style (3.75), correct grammar (3.67), the appropriate synonym to paraphrase (3.67), and changing the active sentence to the passive voice and vice versa (3.54). It can also change the source text's sentence structure (3.46), use proper tenses in literature reviews (3.38), and use proper discourse markers (3.33). Finally, students of the MELE study program can change the source text. Despite the numerous advantages of online paraphrasing tools, students are unable to read or comprehend text, which is the first step in the paraphrasing process.